Dermokine contributes to epithelial–mesenchymal transition through increased activation of signal transducer and activator of transcription 3 in pancreatic cancer. Issue 11 (15th September 2017) - Huang, Chaohao; Xiang, Yukai; Chen, Shengchuan; Yu, Huajun; Wen, Zhengde; Ye, Tingting; Sun, Hongwei; Kong, Hongru; Li, Dapei; Yu, Dinglai; Chen, Bicheng; Zhou, Mengtao
Abstract : Dermokine (DMKN) was first identified in relation to skin lesion healing and skin carcinoma. Recently, its expression was associated with pancreatic cancer tumorigenesis, although its involvement remains poorly understood. Herein, we showed that DMKN loss of function in Patu‐8988 and PANC‐1 pancreatic cancer cell lines resulted in reduced phosphorylation of signal transducer and activator of transcription 3, and increased activation of ERK1/2 and AKT serine/threonine kinase. This decreased the proliferation ability of pancreatic ductal adenocarcinoma (PDAC) cells. In addition, DMKN knockdown decreased the invasion and migration of PDAC cells, partially reversed the epithelial–mesenchymal transition, retarded tumor growth in a xenograft animal model by decreasing the density of microvessels, and attenuated the distant metastasis of human PDAC in a mouse model. Taken together, these data suggested that DMKN could be a potential prognostic biomarker and therapeutic target in pancreatic cancer. Abstract : DMKN mRNA and protein expression correlate with tumor invasion and metastasis Reduced expression of DMKN diminishes growth of tumors DMKN is a potential target of MAPK/ERK1/2 and PI3K/AKT signaling pathways